Relaciones entre algunas características físicas, químicas y nutricionales de maíces latinoamericanos normales y con el gel Opaco-2 y Harinoso-2 - Gómez Brenes, R.; Nettleton, J. A; Núñez, M. J; Olivares, M. J; Poey, Federico; BRESSANI, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Differences in the distribution of physical fractions and of nitrogen in maize samples of normal genetic composition, as well as in Opaque-2 and Floury-2 maize are reported. The results indicate that Opaque-2 maize contains a larger germ than a normal maize, and that it contributes greater amounts of nitrogen. This, together with a greater content of lysine and tryptophan in the endosperm of Opaque-2 maize than in the normal grain, may explain the significantly higher-quality value of the protein of Opaque-2 in comparison with that of the normal samples. Floury-2 maize also has a large-germ, wich is propably the responsible factor of the higher protein content of the kernel, although not as significant as that found in Opaque-2 maize. A fast chemical methodology useful to detect differences between normal and Opaque-2 maize requiring only small amounts of samples is also presented. The study reavealed that a nitrogen fraction, at present called "non protein nitrogen fraction" and free lysine are contained in significantly greater amounts in Opaque-2 than in normal maize. Biological tests carried out in rats confirmed the greater PER values of Opaque-2 maize in comparison with those of normal and Floury-2 samples. Likewise, those animals fed maize, had slightly lower blood urea levels when Opaque-2 was administered than when normal or Floury-2 maize were used as rations. However, at present this method is not sufficiently sensitive to use as a screening tool for the selection of varieties of improved nutritive value.